Optimization of flotation of the Qaleh Zari mine oxidized copper ore sample by the sequential sulfidation approach using the response surface method technique (Rudarsko-geološko-naftni zbornik, 2023)
One of the main challenges in the copper oxide processing industry is the application of flotation to reduce operating costs. Sulfidation-flotation is a commonly employed approach for floating oxide minerals using sulfidizers in order to sulfide the mineral’s surface. In this research work, an oxidized sample from the Qaleh Zari copper mine was used which was a high grade with 5.4% of copper (malachite and azurite). The prepared sample was subjected to mineralogical studies, and the obtained results indicated that the sample was oxidized. Malachite and azurite were the predominant minerals of copper oxide, and the predominant waste minerals were quartz and iron oxides (hematite and magnetite). The addition of sodium sulfide and flotation in four consecutive steps was a successful approach to meet the proper recovery and grade. Sodium sulfide, amyl potassium xanthate, sodium sulfide preparation time, and pH were selected as operating parameters using a central composite design (CCD). Also, by measuring the zeta potential, the electric charge of malachite was determined in different conditions after adding chemicals. Finally, under optimal conditions, the consumptions of sodium sulfide and amyl potassium xanthate, sodium sulfide preparation time, and pH value were 6790 g/t, 736 g/t, 10 minutes, and 9, respectively. By applying the mentioned conditions, a concentrate with a grade of 22.13%Cu and 90.51% recovery was achieved.